Insecurity, Curriculum Implementation and forms of Education in Nigeria (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This paper examined the impact of insecurity on school curriculum implementation in various forms of education (basic education, post-basic education and career development (PBECD) and tertiary education) in the Nigerian schools. Secondary data were to support the points raised in the paper. The data were collected from print resources and online publications. The paper concluded that insecurity is inimical to the development of education in Nigeria. Insecurity specifically has affected curriculum implementation of basic education, post-basic education and career development (PBECD) and tertiary education in Nigerian schools. Also, insecurity has led to unstable academic calendar, death of teachers, researchers and students and poor implementation of curriculum. Based on these points, the paper hereby recommends that government should address all factors breeding insecurities in Nigeria. Government should employ more security officers and deploy to all educational institutions. Government should increase funding of education to enable school administrators to procure security gadget (information communications technologies and artificial intelligence).